New records of helminths of Sceloporus pyrocephalus Cope - Oca, Edgar Uriel Garduño-Montes de; López-Caballero, Jorge D; Mata-López, Rosario (ZooKeys, 2017)
A total of 61 specimens of the Red-headed Spiny Lizard Sceloporus pyrocephalus Cope (Phrynosomatidae) collected during the breeding season (June/July 2003, 2004 and 2005) from Western Mexico were examined for helminths. The morphological characterization of the helminths found was made through light microscopy and scanning electron microscopy. Nine taxa of helminths were identified, two cestodes: Mesocestoides sp. and Oochoristica sp., and seven nematodes: Parapharyngodon ayotzinapaensis Garduño-Montes de Oca, Mata-López & León-Règagnon, 2016, Parapharyngodon tikuinii Garduño-Montes de Oca, Mata-López & León-Règagnon, 2016, Parapharyngodon sp., Physalopterinae gen. sp., Skrjabinoptera scelopori Caballero-Rodríguez, 1971, Strongyluris similis Caballero, 1938 and a new species of Thubunaea Seurat, 1914. Larvae of Mesocestoides sp. and Physalopterinae gen. sp. were found in the body cavity and digestive tract, respectively. Excluding the species of Parapharyngodon Chatterji, 1933, S. pyrocephalus is recorded for the first time as a host of the remaining seven taxa of helminths. Additionally, Thubunaea leonregagnonae sp. n. is described and illustrated as a new nematode species, parasite of S. pyrocephalus from Mexico. This new species can be differentiated from the majority of its congeners by the absence of spicules, the particular pattern of caudal papillae in males and the small ratio of oesophagus length:male total body length (0.1-0.16).